Effect of Functional Capacity Evaluation information on the judgment of physicians about physical work ability in the context of disability claims - Wind, Haije (Springer-Verlag, 2009)
PURPOSE: To test whether Functional Capacity Evaluation (FCE) information lead insurance physicians (IPs) to change their judgment about the physical work ability of claimants with musculoskeletal disorders (MSDs). METHODS: Twenty-seven IPs scored twice the physical work ability of two claimants for 12 specified activities, using a visual analogue scale. One claimant performed an FCE, the other served as a control. Outcome measure was the difference between experimental and control group in number of shifts in the physical work ability for the total of 12 specified activities. RESULTS: The IPs changed their judgment about the work ability 141 times when using FCE information compared to 102 times when not using this information (P-value = 0.001), both in the direction of more and less ability. CONCLUSIONS: The IPs change their judgment of the physical work ability of claimants with MSDs in the context of disability claim procedures more often when FCE information is provided.